Impact of a 3-year mass drug administration pilot project for taeniasis control in Madagascar. - Noromanana Sylvia Ramiandrasoa; Pascaline Ravoniarimbinina; Armand Rafalimanantsoa Solofoniaina; Iharilanto Patricia Andrianjafy Rakotomanga; Samuel Hermas Andrianarisoa; Sophie Molia; Anne-Marie Labouche; Anna Sophie Fahrion; Meritxell Donadeu; Bernadette Abela-Ridder; Davidra Rajaonatahina (Public Library of Science (PLoS), 2020)
Taenia solium is endemic in Madagascar and presents a significant burden on the population and the health system. The parasite cycles through humans who host the adult tapeworm, and pigs that host the larval stages. Accidental infection of humans may occur with the larval stages which encyst in the nervous central system causing neurocysticercosis, a major cause of seizure disorders and a public health problem. One of the interventions to facilitate the control of the disease is mass drug administration (MDA) of the human population with taeniacide. Here we describe a pilot project conducted in Antanifotsy district of Madagascar from 2015 to 2017 where three annual rounds of MDA (praziquantel, 10mg/Kg) were undertaken in 52 villages. Changes in the prevalence of taeniasis were assessed before, during and after the treatments. A total of 221,308 treatments were given to all eligible people above 5 years of age representing a 95% coverage of the targeted population. No major adverse effects were notified related to the implementation of the MDA. The prevalence of taeniasis was measured using Kato-Katz and copro-antigen techniques. Analyses undertaken combining the results of the Kato-Katz with copro-antigen, or using the Kato-Katz results alone, showed that there was a significant reduction in taeniasis 4 months after the last MDA, but 12 months later (16 months after the last MDA) the taeniasis prevalence had returned to its original levels. Results of the pilot project emphasize the need of a multi-sectorial One-Health approach for the sustained control of T. solium.